In search of authenticity : from Kierkegaard to Camus - Golomb, Jacob (London ; New York : Routledge, 1995)
Great philosophers such as Kierkegaard, Nietzsche and Sartre have clearly been preoccupied by the possibility of authenticity. In this study, Jacob Golomb looks closely at the literature and writings of these philosophers in his analysis of their ethics.
Authenticity, sincerity and honesty; authenticity, literature and irony; Kierkegaard's ironic ladder to authentic faith; Nietzsche's pathos of authenticity; Heidegger's ontology of authenticity; Sartre - from phenomenological ontology to psychoanalysis and politics; Camus's return to authentic human morality. Conclusion - authenticity and ethics.
Includes bibliographical references (p. 207-211) and index.
BIED
Karim International
Keywords: Authenticity (Philosophy); Existential ethics